Factors influencing the online book purchase behaviour: a conceptual map on Malaysian Muslim students - Momen, Md Abdul; Haque, A. K. M. Ahasanul; Hossain , Dewan Mahboob; Sultana, Seyama (2014)
The purpose of the study is to assess the factors affecting online book purchase behavior among the Malaysian Muslim students. The study is conceptual in nature. It uses the extensive literature review to configure a conceptual map that influences Malaysian Muslim students’ online book purchase behavior. with the exclusive exploration of prior research, the study come to set up a mind map where it finds four basic underlying factors that influence online book purchase behavior of Malaysian Muslim students. An extensive review of the relevant literatures finds service quality, product information, site awareness and consumers’ security perception as the fundamental factors affecting this behavior. The literature review of the study is comprehensive to extract the associated factors of the online book purchase behavior. Since Malaysia is multiracial country, a further study can be conducted empirically taking different races such as Malay, Indian and Chinese as the moderating factor. Though online purchasing has become very common in Malaysia and many studies have conducted research on the issues from the general perspectives, not much studies have been done to address the specific issue like online book purchase behavior where it is an important phenomena to understand if the Muslim students have tendency to purchase book online, If they have, what are the factors they emphasize more. Since it is hypothesized that Muslims are not quite similar to other people due to their distinct social and religious values and practice, the study will give a new milieu to the key stakeholders about the online book purchase behavior of Muslim students. Hence, the study can set an important notion for the future Muslim consumer research.